The End of Casual: Long Live Casual. Issue 2 (March 2019) - Chess, Shira; Paul, Christopher A.
This special issue is meant to provide an intervention. We are undertaking this project to broaden the corpus of Games Studies by both critiquing casual as a label, yet simultaneously legitimizing it as an important category of both study and play. Additionally, historicizing the terms casual and hardcore as categories uncovers the ways that the video game industry talks about its products and how academic work often replicates biases against casual games. To this end, we argue that the centrality of core games pushes many important texts to the margins. It is our goal, within this special issue, to revalue and reconsider the role of casual games within the larger ecology of game studies.